Ca2+ Signaling, Mitochondria and Cell Death - Rizzuto, Rosario; Giorgi, Carlotta; Romagnoli, Anna; Pinton, Paolo (Current Molecular Medicine, 2008)
In the complex interplay that allows different signals to be decoded into activation of cell death, calcium (Ca2+) plays a significant role. In all eukaryotic cells, the cytosolic concentration of Ca2+ ions ([Ca2+]c) is tightly controlled by interactions among transporters, pumps, channels and binding proteins. Finely tuned changes in [Ca2+]c modulate a variety of intracellular functions ranging from muscular contraction to secretion, and disruption of Ca2+ handling leads to cell death. In this context, Ca2+ signals have been shown to affect important checkpoints of the cell death process, such as mitochondria, thus tuning the sensitivity of cells to various challenges. In this contribution, we will review (i) the evidence supporting the involvement of Ca2+ in the three major process of cell death: apoptosis, necrosis and autophagy (ii) the complex signaling interplay that allows cell death signals to be decoded into mitochondria as messages controlling cell fate.
Keywords: Calcium